Perkembangan Perkembangan Pendidikan Zaman Yunani dan Romawi Hingga Abad Pertengahan di Eropa - Kusmawati, Heny; Salwa, Zakya Ma’rifatus; Ramadhani , Bintang Aura (PT Literasi Nusantara Publisher, 2023)
This article aims to understand how education developed during the ancient Greek and Roman eras to the Middle Ages in Europe. The development of education that was carried out until the Middle Ages had many different learning systems that were carried out. In the development of the value of ancient Greek character education, much was influenced by the thoughts of influential philosophical figures of the time. Whereas in ancient Roman times, this education had values such as the goodness of the motherland, respect for gods, loyalty, quality behavior and stability. So that the Middle Ages was a period of history in Europe with the development of educational character that was carried out so that it could make a wider educated society from time to time.